(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
The aim of this research is to use Municipal Solid Waste (MSW) prepared from the pyrolysis at 450 â°C for the removal of cationic dye (Rhodamine B) in aqueous solution. The effects of contact time and reaction temperature were studied in a batch setup. Scanning Electron Microscopy (SEM) and Fourier Transform Infrared (FTIR) Spectroscopy were used to characterize the modified Biochar and non modified Biochar in order to predict the morphological properties and structural modification respectively. It was found that initial dye concentration (10mg/L), adsorbent dosage (0.3g) and contact time (100minutes) were found to give the highest removal of dye from the adsorbents. Subsequently, it was observed that an increase in the reaction parameters showed an increasing trend for the removal of dye. SEM analysis showed distinct morphology for the fresh and spent adsorbent which was linked to potential clogging resulting from uptake of pore sites by the dyes. The adsorption isotherms showed that the adsorption equilibrium data obeys Langmuir adsorption Isotherm with the maximum monolayer adsorption capacity of 20.30 mg/g and 20.23 mg/g and Pseudo Second Order kinetic model best described the experimental findings for the two adsorbents used in the study. Moreover, thermodynamic study reveals that the adsorption is a spontaneous and exothermic process